2014
DOI: 10.1634/theoncologist.2014-0042
|View full text |Cite
|
Sign up to set email alerts
|

European Perspective on Multiple Myeloma Treatment Strategies in 2014

Abstract: The treatment of multiple myeloma has undergone significant changes and has resulted in the achievement of molecular remissions,the prolongation of remission duration, and extended survival becoming realistic goals, with a cure being possible in asmallbut growing numberof patients.Inaddition, nowadaysit is possible to categorize patients more precisely into different risk groups, thus allowing the evaluation of therapies in different settings and enabling a better comparison of results across trials. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
87
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 141 publications
1
87
0
2
Order By: Relevance
“…21 Other studies have confirmed the relevance of assessing frailty, quality of life and physical activity. 18,32,34,35 The assessment of organ function, such as renal and lung impairment, has shown to influence survival rates, treatment toxicity and early death. 8,16,36 Moreover, tumor genetics have been reported to relevantly influence the clinical heterogeneity of MM.…”
Section: P=00054mentioning
confidence: 99%
“…21 Other studies have confirmed the relevance of assessing frailty, quality of life and physical activity. 18,32,34,35 The assessment of organ function, such as renal and lung impairment, has shown to influence survival rates, treatment toxicity and early death. 8,16,36 Moreover, tumor genetics have been reported to relevantly influence the clinical heterogeneity of MM.…”
Section: P=00054mentioning
confidence: 99%
“…With most patients receiving a backbone therapy of an IMiD and dexamethasone or a PI and dexamethasone, the development of disease that is refractory to one or both of these classes is a concern in RRMM. A key question following the development of refractory disease is whether to switch the class of agent from the previous line or to switch to another treatment option within the same class of agent (Ludwig et al, 2014).…”
Section: Patients With Refractory Disease: Switching Within and Betwementioning
confidence: 99%
“…Originally developed for the study of proteasome physiology, proteasome inhibitors soon demonstrated significant antineoplastic activity (2) that, starting with bortezomib, was successfully applied in the treatment of multiple myeloma (3). Subsequently, bortezomib has become an almost indispensable part of the gold standard therapy regimen, significantly improving the treatment outcomes of affected patients (4). However, its clinical applicability is considerably impeded by dose-limiting toxicity (5) and by primary or secondary drug-resistance (6,7).…”
Section: Introductionmentioning
confidence: 99%